Enterprise risk management - Fraser, John R. S., 1946- (Wiley, 2010)
Essential insights on the various aspects of enterprise risk management. If you want to understand enterprise risk management from some of the leading academics and practitioners of this exciting new methodology, Enterprise Risk Management is the book for you. Through in-depth insights into what practitioners of this evolving business practice are actually doing as well as anticipating what needs to be taught on the topic, John Fraser and Betty Simkins have sought out the leading experts in this field to clearly explain what enterprise risk management is and how you can teach, learn, and imple.- Resumé vydavatel
Keywords: rizikový management; risk management; elektronické knihy; monografie; electronic books; monographs